2023
DOI: 10.3390/jfb14090452
|View full text |Cite
|
Sign up to set email alerts
|

A New α + β Ti-15Nb Alloy with Low Elastic Modulus: Characterization and In Vitro Evaluation on Osteogenic Phenotype

Tatiani Ayako Goto Donato,
Karolyne dos Santos Jorge Sousa,
Pedro Akira Bazaglia Kuroda
et al.

Abstract: This study aimed to produce Ti-15Nb alloy with a low elastic modulus, verify its biocompatibility, and determine whether the alloy indirectly influences cellular viability and morphology, as well as the development of the osteogenic phenotype in cells cultured for 2, 3, and 7 days derived from rat calvarias. Two heat treatments were performed to modify the mechanical properties of the alloy where the Ti-15Nb alloy was heated to 1000 °C followed by slow (−5 °C/min) (SC) and rapid cooling (RC). The results of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Thus, it can be observed that the elastic modulus of the alloys studied in this work is closer to the human bone than the traditional alloys used [6,30,[43][44][45][46]. It is essential to highlight that a low modulus value is required to produce new metals for biomedical use to avoid the "stress shielding" effect.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it can be observed that the elastic modulus of the alloys studied in this work is closer to the human bone than the traditional alloys used [6,30,[43][44][45][46]. It is essential to highlight that a low modulus value is required to produce new metals for biomedical use to avoid the "stress shielding" effect.…”
Section: Discussionmentioning
confidence: 89%